PSİKOJENİK POLİDİPSİNİN NEDEN OLDUĞU BİR HİPONATREMİK ENSEFALOPATİ OLGUSU - CEYHAN DİRİCAN, Ayten and ALTUNKAYNAK, Yavuz and ÇELİK, Selma and MUTLUAY, Belgin and COŞKUN, Kerem and KÖKSAL, Ayhan and BAYBAŞ, Sevim (Cerrahpaşa Medical Journal, 2014)
Background.- In psychiatric diseases excessive water drinking in a short time is known as psychogenic polydipsy. In this instance water can not be excreted from kidneys, which leads to water intoxication complicated with severe neurological findings and high mortality. We report a 31-year-old female patient known to be mentally retarded and psychotic. She was admitted to our clinic with hyponatremic encephalopathy. She was evaluated as psychogenic polydipsy due to water intoxication. This entity is a well known rare condition. Herewith we report our case as a rare sample.